The Use of Cell-free Protein Synthesis to Push the Boundaries of Synthetic Biology - Kim, Kyu Jae; Lee, So-Jeong; Kim, Dong-Myung (Biotechnology and bioprocess engineering, 2023)
Cell-free protein synthesis is emerging as a powerful tool to accelerate the progress of synthetic biology. Notably, cell-free systems that harness extracted synthetic machinery of cells can address many of the issues associated with the complexity and variability of living systems. In particular, cell-free systems can be programmed with various configurations of genetic information, providing great flexibility and accessibility to the field of synthetic biology. Empowered by recent progress, cell-free systems are now evolving into artificial biological systems that can be tailored for various applications, including on-demand biomanufacturing, diagnostics, and new materials design. Here, we review the key developments related to cell-free protein synthesis systems, and discuss the future directions of these promising technologies.